Dielectric behavior of porous PMMA: From the micrometer to the nanometer scale. (19th December 2016) - Notario, B.; Pinto, J.; Verdejo, R.; Rodríguez-Pérez, M.A.
Abstract: In recent years, there has been a significant interest of the scientific community on nanocellular polymeric foams as a possible next generation of materials with a low dielectric constant for microelectronics applications In this work, the dielectric behavior of microcellular and nanocellular poly (methyl methacrylate) (PMMA) based foams has been characterized, both as a function of frequency and temperature, in order to analyze the effect of reducing the cell size to the nanoscale on the dielectric properties. Experimental results have shown clear differences in the dielectric behavior of the samples with cell sizes in the nanoscale as well as a sharp reduction of the dielectric constant when the porosity increases. Graphical abstract: Highlights: Dielectric behavior of micro and nanocellular PMMA foams has been characterized. A sharp reduction of the dielectric constant with porosity was obtained. Differences in cell size results in clear differences in the dielectric behavior.